2013
DOI: 10.1021/sb400052f
|View full text |Cite
|
Sign up to set email alerts
|

Biological Noise Abatement: Coordinating the Responses of Autonomous Bacteria in a Synthetic Biofilm to a Fluctuating Environment Using a Stochastic Bistable Switch

Abstract: Noise is inherent to single cell behavior. Its origins can be traced to the stochasticity associated with a few copies of genes and low concentrations of protein and ligands. We have studied the mechanisms by which the response of noisy elements can be entrained for biological signal processing. To elicit predictable biological function, we have engineered a gene environment that incorporates a gene regulatory network with the stringently controlled microenvironment found in a synthetic biofilm. The regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…For example, due to crosstalk, the lux-genes in V. fischeri do not seem to discriminate between 3OC 6 HSL and C 8 HSL so that lux regulation can become noisy, 40 which could be used to suppress or even enhance the sensitivity of a gene switch. 14,39 What is new in this report is that information (associated with the pulses of inductants, IPTG and arabinose) was transmitted in isolated channels by diffusion of QS signal molecules to receivers with embedded memory, and coordinated through the precise placement of the transmitting and receiving elements and inductant clock pulses to create predictable responses. Diffusive, dispersive signal transmission like this also 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 occurs in dendritic processes in neurons, which form the basis for information processing in the nervous system.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…For example, due to crosstalk, the lux-genes in V. fischeri do not seem to discriminate between 3OC 6 HSL and C 8 HSL so that lux regulation can become noisy, 40 which could be used to suppress or even enhance the sensitivity of a gene switch. 14,39 What is new in this report is that information (associated with the pulses of inductants, IPTG and arabinose) was transmitted in isolated channels by diffusion of QS signal molecules to receivers with embedded memory, and coordinated through the precise placement of the transmitting and receiving elements and inductant clock pulses to create predictable responses. Diffusive, dispersive signal transmission like this also 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 occurs in dendritic processes in neurons, which form the basis for information processing in the nervous system.…”
Section: Resultsmentioning
confidence: 93%
“…It has been shown that LuxR, in combination with this promoter, positively auto-regulates the QS response by modulating its own expression. 14,30,42 While luxP(R) had only a low-level basal expression, it was strongly up-regulated in the presence of the luxR-3OC 6 HSL dimer and produced a variant of green fluorescent protein, GFP-LVA, in this case. GFP-LVA was unstable; it degraded by proteolytic digestion with a half-life of about 10-20 min.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations